Hematite Nanoparticles Synthesized by Green Route: Characterization, Anticancer and Antioxidant Activities - Safa Ezzine; Hela Ferjani; Oluwasayo E. Ogunjinmi; Damian C. Onwudiwe (Inorganics)
Recently, attention has shifted towards the green synthesis of nanoparticles using plant extracts rich in phytochemicals like phenols and flavonoids, offering an alternative method that avoids harmful chemicals and enables large-scale, low-cost production. This study introduces a straightforward and eco-friendly approach to synthesizing hematite α-Fe2O3 nanoparticles utilizing an aqueous extract of Musa paradisiaca. The variation in the calcination temperature resulted in the formation of nanoparticles presented as Fe2O3 (1), Fe2O3 (2), and Fe2O3 (3), obtained at 650, 750, and 900 °C for 4 h, respectively. This variation allowed for an investigation into the impact of different reaction temperatures on the structural and optical properties of the nanoparticles. Structural analysis was conducted using X-ray diffraction (XRD), while scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were employed to examine morphology. Optical properties were assessed via UV-vis spectroscopy, revealing a reduction in the energy band gap (from 2.5 to 1.87 eV), attributed to an increase in crystallite size resulting from longer calcination temperatures (650–900 °C). A biological assay was carried out to evaluate the antioxidant and anticancer potentials of the nanoparticles. Both Fe2O3 (1) and Fe2O3 (2) with IC50 values of 46.84 and 46.14 µg/mL, respectively, showed similar antioxidant potentials, while peel extract exhibited the least activity with an IC50 of 79.26 µg/mL. The nanoparticles, peels, and 5-FU (used as standard) showed a stronger inhibitory effect on the Human Embryonic Kidney (HEK) 293 cells compared to the HeLa cells. This implies that the HEK 293 cells might be more susceptible to the drug samples and a lower concentration might even be sufficient to achieve the inhibition of normal cell proliferation. These results indicate a better therapeutic window with a lesser inhibitory effect compared to standard drugs used as controls.